INCAL '98 proceedings... - The Aluminium Association of India; International Conference on Aluminium New Delhi, India February 11 - 13 1998; Sastry, D. H. [ed.]; Subramanian, S. [ed.]; Murthy, K. S. S. [ed.]; Abraham, K. P. [ed.] (Bangalore Anubhava Printers, 1998)
Aluminium ; Eco-friendly metal of the 21st century
Keywords: Aluminium; Eco - friendly metal